REVIEW ARSITEKTUR BIOLOGIK INTEGRAL UNTUK PERANCANGAN BANGUNAN DI DAERAH TROPIK - Mochammad Yusuf Hariagung (Purifikasi, 2006)
Internal biological architecture is architecture in which natural life (bios) and instinctive (logos) are integrally carried out. To achieve the objective, it is necessary to be able to understand and assess. Problems in development of internal biological architectures among others are protection against weather, animals, and pathogenics. The life quality depends on developments and occupants, lands, plants, environments, climates, traditions, local life, development and dwelling, as well as cultures. In order to realize the protected and functional dwellings, it is necessary to take “metamodel” of integral biological architecture into account to come out with new ways towards planning, development, dwellings and life in which human beings play prominent roles to unite and integrate the factors. Biological architecture begins with biological development and ends with ecologically and alternatively deeper new thinking and oriented to the future whose life, education and dwellings are balanced with nature.